2011
DOI: 10.2118/148945-pa
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Experiment on Coalbed-Methane Desorption Influenced by Water Injection and Temperature

Abstract: Summary Traditional coalbed-methane (CBM) exploitation technologies, including ordinary drills, enhanced drills, water jets, and hydrofracture in the coalbed, are widely used in modern coal mining and involve high-pressure water. Because the CBM-desorption capacity decreases when using high-pressure water, the CBM output efficiency is lower than expected. To investigate the decrease in CBM desorption after water injection and the increase in CBM output after temperature is raised, an experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…When the pore radius is smaller, the capillary force is larger, and the hysteresis is more obvious. Similarly, Zhao (2011) [21] has carried out several experiments to study the methane desorption from coals Љconfined by waterЉ, his results show that desorption rate is related to water content, and for coals with high water content, it will be less than 13% due to the effect of capillary force, which coincides with our analysis. Therefore, in CBM reservoirs, the influence of capillary pressure on desorption should not be ignored.…”
Section: Spe-177001-mssupporting
confidence: 87%
See 2 more Smart Citations
“…When the pore radius is smaller, the capillary force is larger, and the hysteresis is more obvious. Similarly, Zhao (2011) [21] has carried out several experiments to study the methane desorption from coals Љconfined by waterЉ, his results show that desorption rate is related to water content, and for coals with high water content, it will be less than 13% due to the effect of capillary force, which coincides with our analysis. Therefore, in CBM reservoirs, the influence of capillary pressure on desorption should not be ignored.…”
Section: Spe-177001-mssupporting
confidence: 87%
“…(1) for three sets of experiments is only 3.36%, 4.98% and 4.21%, respectively (Fig.4). Actually, a similar experiment has been carried out by Zhao(2011) [21] , in his study, methane was firstly adsorbed into coal pore systems at a certain equilibrium pressure, and then liquid water was injected into the container with coal and adorbed gas until it was full of water. Finally, methane desorption from the aqueous environment was performed.…”
Section: Experiments Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, if high pressure water has been injected into coalbed, the desorption capacity of methane would be effected due to moisture. (Zhao et al, 2011) Some researchers have engaged in this field in order to improve coalbed permeability and amount of gas output. The two major technologies are hydraulic fracture and thermal injection.…”
Section: Introductionmentioning
confidence: 99%
“…According to the mechanism of moisture increased in coalbed, many scholars have performed studies on the influence of moisture on methane desorption (Xie et al 2011;Zhang and Sang 2009), but they wet the coal samples before the experiment. Some scholars realized that injecting water would destroy the statement for gas adsorption (Pakowski et al 2011;Xiao and Wang 2011;Zhang et al 2011a;Zhao et al, 2011;Chen et al, 2015), and they designed the ideal experimental process in which water was injected into the dry coal samples under the equilibrium state of gas absorption. All of these results showed that the maximum desorption quantity decreases gradually with the amount of injected water, but they were not considering different water pressure impacted on same or different equilibrium gas adsorption state.…”
Section: Introductionmentioning
confidence: 99%